FREQUENCY OF CYSTOID MACULAR EDEMA ON OPTICAL COHERENCE TOMOGRAPHY IN TWO DIFFERENT TYPES OF CATARACT SURGERY - KAMRAN , MS; AHMAD , W; KAMRAN , MK; AHMAD , M (Biological and Clinical Sciences Research Journal, 2024)
Cystoid macular edema (CME), also known as Irvine-Gass syndrome, has been recognized as a non-specific manifestation of various ocular conditions, with cataract surgery being a significant contributing factor. First reported by Sir Irvine in 1953 and further discussed by Sir Norton in 1966, CME following cataract surgery remains a topic of interest and concern in ophthalmology. The precise etiology of CME in post-cataract surgery patients remains elusive; however, it is widely accepted that post-surgical inflammation plays a pivotal role. To address this issue, we conducted a comparative study to assess the frequency of CME using spectral-domain optical coherence tomography (SD-OCT) in patients undergoing extracapsular cataract extraction (ECCE) versus phacoemulsification cataract surgeries. The study was conducted at the Department of Clinical Ophthalmology, Khyber Institute of Ophthalmic Medical Sciences; Medical Teaching Institute Hayatabad Medical Complex, Peshawar, over a period of 6 months. Utilizing a randomized controlled trial design and non-probability consecutive sampling, we determined a sample size of 70 patients, with 35 patients allocated to each group (Group A: ECCE, Group B: Phacoemulsification). The age of the participants ranged from 50 to 85 years, with a median of 60 years and a mean of 65±8 years. Our findings revealed that CME was observed in 11% of patients in Group A and 6% in Group B, indicating a lower frequency in post-operative cases. However, the difference in CME incidence between ECCE and phacoemulsification cases was not statistically significant. These results suggest that the risk of CME in post-operative cases may be influenced by various factors, including surgical technique and patient-specific variables. In conclusion, our study contributes to the understanding of CME following cataract surgery and underscores the importance of continued vigilance and further research in this area. Improved surgical techniques and perioperative management may help mitigate the risk of CME and enhance patient outcomes in the postoperative period.